2020
DOI: 10.1186/s12888-020-02950-0
|View full text |Cite
|
Sign up to set email alerts
|

Should we increase the focus on diet when considering associations between lifestyle habits and deliberate self-harm?

Abstract: Background Despite increasing awareness of high rates of physical illness and poor lifestyle behaviours among patients with a history of repeated deliberate self-harm (DSH), there is little research on specific lifestyle factors that are potentially problematic for this group. This paper aims to explore the relationship between lifetime repeated DSH and certain lifestyle factors, including balanced meals, eating breakfast, consumption of ‘junk’ food, weight, exercise, substance/alcohol use, smoking and social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Latina et al [ 24 ] found that adolescents who engaged in organized sports activities were more likely to have increased self-esteem one year later and a decreased likelihood of self-harming behaviours. Berg et al [ 5 ] found that poor diets were associated with increased risks of deliberate self-harm episodes. Agathão et al [ 3 ] found that a lack of family meals was associated with a higher frequency of mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Latina et al [ 24 ] found that adolescents who engaged in organized sports activities were more likely to have increased self-esteem one year later and a decreased likelihood of self-harming behaviours. Berg et al [ 5 ] found that poor diets were associated with increased risks of deliberate self-harm episodes. Agathão et al [ 3 ] found that a lack of family meals was associated with a higher frequency of mental disorders.…”
Section: Discussionmentioning
confidence: 99%